(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Greece exhibits one of the highest rates of deaths and injuries due to motor vehicle crashes in young adults in Europe. The personal, social and financial cost is still very high as road traffic crashes account for 65.8% of all deaths among young people aged 10-24 years, with prominent gender differences that are not fully explained yet. Methods: using a descriptive cross-sectional study design, we examined the associations of seatbelt and helmet use with the likelihood of manifesting multiple driving violations (fail to stop at STOP signs, running red traffic lights, driving towards the wrong direction, illegal overtaking, speeding, cellphone use while driving, driving under the influence of alcohol) in a sample of 536 1st year university students in Greece. A ‘Risky Driving Index’ score (RDI) was produced by summing the frequencies of all behaviours (range 0-28). Results: only 8.8% of the students reported not performing any of the driving violations, whereas 8.6% engaged in all 7 of them when driving (male: 11.5%; female: 1.9%; score>8, male: 31.7%; female: 8.1%). Male, but not female participants, who never used seatbelts and helmets, reported significantly higher RDI scores with evidence of a dose-response effect in the increase. In adjusted logistic regression models, those who never used (vs regular use) seat belt ‘as drivers’ and ‘as rear seat passengers’ had increased odds of being in the higher score category of RDI (OR=5.239 95%CI=1.280-21.441 and OR=6.782 95%CI=1.891-24.324, respectively). Conclusion: young male drivers and riders, but not their female counterparts, that do not take typical safety measures (seatbelt and helmet use), reported more illegal and risky driving behaviours. Preventive interventions using a gender-informed approach are needed to address co-occurring risk driving behaviours.